2013
DOI: 10.3109/15376516.2012.754534
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of toxicity by carbon nanotubes

Abstract: Carbon nanotubes (CNTs) consist of a family of carbon built nanoparticles, whose biological effects depend on their physical characteristics and other constitutive chemicals (impurities and functions attached). CNTs are considered the twenty first century material due to their unique physicochemical characteristics and applicability to industrial product. The use of these materials steadily increases worldwide and toxic outcomes need to be studied for each nanomaterial in depth to prevent adverse effects to hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 152 publications
1
29
0
Order By: Relevance
“…Mechanisms of action reported for MWCNT are 'frustrated phagocytosis' (i.e. stiff, non-degradable MWCNT overwhelming the phagocytic capacity of tissue macrophages thereby causing chronic tissue inflammation) and DNA oxidative injury, generation of ROS due to the metal impurities trapped inside the carbon nanotubes, pro-inflammatory effects due to oxidant injury, and pro-fibrogenic responses, and the intensitiy of these effects is reported to change with differing fiber sizes (Damoiseaux et al, 2011;Meng et al, 2009;Nel et al, 2009Nel et al, , 2013aRodriguez-Yanez et al, 2013).…”
Section: Comparison Of Nm Effects In the Pclus Test System To In Vivomentioning
confidence: 95%
See 1 more Smart Citation
“…Mechanisms of action reported for MWCNT are 'frustrated phagocytosis' (i.e. stiff, non-degradable MWCNT overwhelming the phagocytic capacity of tissue macrophages thereby causing chronic tissue inflammation) and DNA oxidative injury, generation of ROS due to the metal impurities trapped inside the carbon nanotubes, pro-inflammatory effects due to oxidant injury, and pro-fibrogenic responses, and the intensitiy of these effects is reported to change with differing fiber sizes (Damoiseaux et al, 2011;Meng et al, 2009;Nel et al, 2009Nel et al, , 2013aRodriguez-Yanez et al, 2013).…”
Section: Comparison Of Nm Effects In the Pclus Test System To In Vivomentioning
confidence: 95%
“…Physico-chemical properties of nanomaterials that have been recognized to influence their inhalability, deposition efficiency, and toxicology are their airborne and hydrodynamic size, size distribution, shape (and aspect ratio), their state of agglomeration, surface properties and functionalization (surface area, porosity, charge, reactivity, chemistry/ coatings, contaminants), as well as solubility and crystallinity (Kuempel et al, 2012;Nel et al, 2013a;Oberdörster, 2009;Oberdörster et al, 1994;Rodriguez-Yanez et al, 2013;Zhu et al, 2013). Also in in vitro cytotoxicity assays, particle size, surface chemistry and coating, as well as chemical composition have been recognized as key determinants of nanoparticle adverse effects (Feltis et al, 2012;Horev-Azaria et al, 2011;Kroll et al, 2011).…”
Section: Particle Characteristics Influencing Particle Effectsmentioning
confidence: 99%
“…Many studies have observed CNTs to be toxic in a number of ways, such as inducing pulmonary toxicity (Lam et al, 2006), inhibiting root growth and elongation (Canas et al, 2008) as well as generating oxidative stress (Rodriguez-Yanez et al, 2013). Strong associations between CNTs and various pollutants significantly alter the bioavailability and toxicity of both CNTs and associated pollutants (Sheng et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…141 It is proposed that the geometry and agglomeration of carbon nanotubes, in addition to their metallic impurities, contribute to their toxicity. 142 Still, we should be cautious to believe that spherical nanoparticles are always safer than tubular structures because the toxicological properties of nanomaterials are very complicated and depend on many different factors. Nonetheless, many current studies on spherical nanocarbon materials support the idea that the spherical shape may be advantageous in many biological systems.…”
Section: Toxicity Of Spherical Nanocarbon Materials-are Spherical Nanmentioning
confidence: 99%